The ethico-politics of design toolkits: responsible AI tools, from big tech guidelines to feminist ideation cards - Hollanek, Tomasz (Springer Science and Business Media LLC, 2024)
AbstractThis paper interrogates the belief in toolkitting as a method for translating AI ethics theory into practice and assesses the toolkit paradigm’s effect on the understanding of ethics in AI research and AI-related policy. Drawing on a meta-review of existing ‘toolkit-scoping’ work, I demonstrate that most toolkits embody a reductionist conception of ethics and that, because of this, their capacity for facilitating change is limited. Then, I analyze the features of several ‘alternative’ toolkits–informed by feminist theory, posthumanism, and critical design–whose creators recognize that ethics cannot become a box-ticking exercise for engineers, while the ethical should not be dissociated from the political. This analysis then serves to provide suggestions for future toolkit creators and users on how to meaningfully adopt the toolkit format in AI ethics work without overselling its transformative potential: how different stakeholders can draw on the myriad of tools to achieve socially desirable results but reject the oversimplification of ethical practice that many toolkits embody.
Keywords: 35 Commerce, Management, Tourism and Services; 50 Philosophy and Religious Studies; 5001 Applied Ethics; 3507 Strategy, Management and Organisational Behaviour